Peran Kepolisian Dalam Menanggulangi Tindak Pidana Pengedaran Obat Secara Illegal (Studi Kasus Polres Gorontalo Kota) - Aryo Putrawan Polamolo; Mohamad Rusdiyanto U Puluhulawa; Suwitno Yutye Imran (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to find out and analyze the role of the police in tackling illegal drug trafficking and find out what obstacles the police face in dealing with illegal drug trafficking at the Gorontalo City Police, based on the title raised in this study, researchers see the weakness of Indonesia's defense From the invasion of things that endanger society, thousands of illegal drugs have been circulating throughout Indonesia. This study uses empirical methods. The data collection process examined by researchers in this study were primary data and secondary data. Data collection techniques that support and relate to this research are interviews, observation and literature studies..The results of this study indicate that the cause of people becoming perpetrators of illegal drug distribution is because they want to get rich quickly, perpetrators take advantage of the lack of public knowledge about illegal drugs and the correct distribution mechanism according to the rules. There are several factors that support perpetrators involved in illegal drug trafficking. , namely: Economic factors and environmental and social factors. Illegal drug distribution in Indonesia is regulated in Law no. 36 of 2009 concerning health. The free circulation of illegal drugs in Indonesia has turned out to be used by many elements to gain large profits. Some transactions also occur online. The opportunity to buy cheap drugs and sell them at high/profitable prices is the motive of several individuals who have been caught in illegal drug trafficking. This will not happen if people are educated about economics and law. This is a joint responsibility of the government, the community, BPOM and the Indonesian National Police.